RANCANG BANGUN SISTEM PENELITIAN DAN PENGABDIAN MASYARAKAT UNIVERSITAS BANGKA BELITUNG BERBASIS WEB SERVER - Ghiri Basuki Putra (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2017)
Tridharma Perguruan Tinggi is Teaching, Research and Community Service that must be implemented by every lecturer. Sources of funding for research and Community Service for university lecturers vary, ranging from university level as well as from the Ministry of Research and Higher Education. At the University of Bangka Belitung (UBB), the process of submitting research proposals and Community Service to lecturers is still done manually and there is no online system to support and simplify the proposal submission process and proposal assessment. As for the national level has been using a system called Information Systems Research and Community Service or abbreviated simlitabmas that can be used by all lecturers in Indonesia in submitting research proposals and Community Service to get funding. In the design of research system and dedication, build a system like simlitabmas from Risetdikti to facilitate lecturers in submitting research proposal of university level online and can be done online proposal assessment by university level accessor also online. In this research, build design Lecturer Research and Service System Based Webserver online. The system is built with a web-based integrated system using PHP and MySQL databases. So without printing the proposal and save the cost of printing and paper, lecturers can make submission of research proposal and community service.